On-Farm Evaluation of Production Potential and Economics of Four Crops Based Cropping Pattern (Bangladesh Agronomy Journal, 2021)
A field experiment was conducted at multi-location testing (MLT) site, Barura under On-Farm Research Division (OFRD), Bangladesh Agricultural Research Institute, Cumilla during 2014-16 to determine the productivity and profitability of cropping patterns, viz. Boro (var. BRRI dhan28)-T.Aus (var. BRRI dhan48)- T. Aman (var. BRRI dhan49)-Fallow (existing cropping pattern) and Boro (var. BRRI dhan28)-T. Aus (var. BRRI dhan48)-T. Aman (var. Binadhan-11)-Mustard (var. BARI Sarisha-14) as  improved cropping pattern. The results showed that improved cropping pattern provided higher amount of grain and by-product yield. The highest mean REY (18.08 t ha-1), PE (54.61 kg ha-1 day-1), LUE (90.68 %) and SYI (77.12%) was obtained from improved cropping pattern Boro-T.Aus-T. Aman-Mustard and the lowest (14.30 t ha-1 in 2014-15 and 13.98 t ha-1 in 2015-16) from farmers existing cropping pattern. The highest gross return (Tk. 274800 ha-1 in 2014-15 and Tk. 276600 ha-1 in 2015-16), gross margin (Tk. 113950 ha-1 in 2014-15 and Tk. 106750 ha-1 in 2015-16) and BCR (1.70 in 2014-15 and 1.66 in 2015-16) were obtained from improved four crops based cropping pattern (Boro-T. Aus-T. Aman-Mustard). Two years results showed that four crops could be grown one after another in a sequence in the farmers field of Cumilla region for achieving higher system productivity and economic return.Bangladesh Agron. J. 2021, 24(1): 101-108